Akulturasi Budaya Lokal Dan Budaya Eropa Pada Bangunan Gereja Kristus Raja Pagal, Kelurahan Pagal, Manggarai, NTT Dan Potensinya Sebagai Sumber Belajar Sejarah Di SMA - Tarsisius Nogu, Gaudensia Yani Nogu; Maryati, Tuty; Yasa, I Wayan Putra (Widya Winayata : Jurnal Pendidikan Sejarah, 2025)
ABSTRACT This study aims to analyze the process of cultural acculturation between Manggarai’s indigenous traditions and European influences through a case study of Christ the King Church in Pagal Village, Manggarai, East Nusa Tenggara. The research background traces back to the European expansion into the archipelago from the 16th century under the “gold, glory, gospel” paradigm, which not only pursued the spice trade but also carried a missionary agenda. In-depth interviews with key informants including a traditional elder, the parish council chair, the parish priest, the village head, administrative staff, and a history teacher revealed that the Pagal community embraced Catholic teachings prior to the arrival of the Dutch and subsequently integrated these with local cultural values. The qualitative methodology employed heuristic source gathering, field observation, structured and spontaneous interviews, and document analysis, followed by source criticism, interpretation, and historiography. architectural analysis highlights the integration of mbaru gendang elements—symbols of Manggarai unity—within the church’s structure and ornamentation, including its dome, nativity scene decorations, and the practice of celebrating mass in traditional attire and local language. this reciprocal process of acculturation has reinforced local identity and promoted values of tolerance, religiosity, and patriotism. the findings recommend leveraging Christ the King Church in Pagal as a historical learning resource for senior high schools to foster character education through an understanding of cultural acculturation.   Keywords: acculturation, church architecture, learning resource, history.